Quantitative phase analysis and crystal structure of DyBCO ceramics prepared at different sintering conditions - Paitoon Boonsong (2018)
© 2018, Chiang Mai University. All rights reserved. The DyBCO ceramics were fabricated by solid-state reaction method under a normal air atmosphere using a stoichiometric amount (i.e. Dy:Ba:Cu = 1:2:3) of high-purity Dy2O3, BaCO3and CuO starting powders, which were previously mixed and calcined at 900°C for 4 h. The green DyBCO pellets were sintered at various sintering temperatures (i.e. 850, 900, 930, 950 and 980°C) for 2 h. The influence of sintering process on phase formation of ceramics was observed by X-ray diffraction (XRD). The quantitative phase analysis of ceramics was analyzed by fitting the XRD pattern using the PowderCell program. The results showed that the DyBa2Cu3O7−βcomposition was identified as the main crystalline phase. At higher temperatures (> 950°C), the Dy2BaCuO5(Dy-211) secondary phase was observed. The relative fraction of various phases was discussed in relation to phase formation and density change. The SEM-EDS/WDS images of ceramics exhibited irregular shaped grains. The average grain size increased from ∼2.3 to ∼7.0 μm when the sintering temperature was increased. The possibility of stoichiometric change in DyBCO ceramic due to different processing conditions was also discussed in details.